ANALISIS PENGARUH PENERIMAAN MANFAAT, NILAI KEUNTUNGAN DAN NORMA SUBJEKTIF TERHADAP MINAT BELI KEMBALI LAYANAN STREAMING MUSIK BERBAYAR (Studi pada Mahasiswa Fakultas Ekonomika dan Bisnis Universitas Diponegoro) - Bintang Saputra, Christophorus; Idris, Idris (Faculty of Economics and Business Diponegoro University, 2018)
The development of the digital era makes it easier for individuals to do music piracy. This gives a big loss for musicians and companies engaged in the music industry. The music streaming service or MSS present gives individuals the option to consume music in a legal way, MSS has two business models, users can listen to music for free with low quality and ad breaks. And users can subscribe by getting more facilities like higher voice quality and without ad breaks, but previous research results state that users of free music streaming services can be associated with piracy. The purpose of this study is to analyze the acceptance of benefits, the value of profit and subjective norms on the interest to buy back paid music streaming service studies on the students of economics faculty and business university diponegoro. The population in this study are active students faculty of economics and business university diponegoro sorted by sampling method. The sample used to represent the population has a total of 150 samples, which consists of 52 management majors, 49 accounting majors, 33 iesp majors and 15 Islamic economics majors. The results of the study found that perceived usefulness had positive and significant effect on the repurchase intention, the perceived value had positive and significant effect on the repurchase intention, and subjective norm have positive and significant influence on the repurchase intention.